Nazi soundscapes : sound, technology and urban space in Germany, 1933-1945 - Birdsall, Carolyn (2012)
Following the formation of the German National Socialist Party in the 1920s, various forms of sound (popular music, voice, noise and silence) and media technology (radio and loudspeaker systems) were configured as useful to the party's political programme. Focusing on the urban "soundscape" of Düsseldorf, the author makes a persuasive case for investigating such sound events and technological devices in their specific contexts of production and reception. Nazi Soundscapes identifies strategies for controlling space and reworking identity patterns, but also the ongoing difficulties in manipulating mediated sounds and the spaces of listening reception, whether in the home, workplace, the cinema, public rituals or with wartime siren systems. The study revises visualist notions of social control, and reveals the disciplinary functions of listening (as eavesdropping) as well as the sonic dimensions to exclusion and violence during Nazism. An essential title for everyone interested in the links between German political culture, audiovisual media and urban history, Nazi Soundscapes provides a fascinating analysis of the cultural significance of sound between the 1920s and early 1940s. Click "http://soundclips.humanities.uva.nl/">here for the sound clips discussed in the book.